Role of lectin pathway complement proteins and genetic variants in organ damage and disease severity of systemic sclerosis: a cross-sectional study - Osthoff, Michael (Arthritis Res Ther, 2019)
BACKGROUND: The role of the complement system in the pathogenesis of systemic sclerosis (SSc) is controversial. This study investigated the role of the lectin pathway of complement as a mediator of ischemia/reperfusion injury in SSc. METHODS: This is a prospective observational cross-sectional study of 211 SSc patients and 29 patients with Raynaud’s phenomenon in undifferentiated connective tissue disease (UCTD) at risk of developing SSc from two outpatient clinics. Serum levels of lectin pathway proteins (FCN-2, FCN-3, MBL, and MASP-2) and eight MBL2 and FCN2 single-nucleotide polymorphisms (SNP) were analyzed by sandwich-type immunoassays and genotyping and examined for their association with disease manifestations. RESULTS: Lectin pathway protein levels and SNPs were similar between SSc and UCTD patients. FCN-2 levels were however higher in SSc patients with present evidence of digital ulcers (mean 1.4 vs. 1.0 μg/mL, p = 0.05), pitting scars (mean 1.3 vs. 1.0 μg/mL, p = 0.01), and puffy fingers (mean 1.2 vs. 1.0 μg/mL, p = 0.04). Similarly, higher FCN-2 levels were observed in SSc patients with Scl-70 autoantibodies (mean 1.5 vs. 1.0 μg/mL, p = 0.001), interstitial lung disease (mean 1.2 vs. 0.9 μg/mL, p = 0.02), and a forced vital capacity (FVC) below 80% (mean 1.4 vs. 1.0 μg/mL, p = 0.02). In line, variant alleles in the FCN-2 SNP at position + 6359 were associated with a significantly reduced FVC and diffusion capacity. Furthermore, patients with SSc renal crisis harbored higher MBL levels (mean 2.7 vs. 1.5 μg/mL, p = 0.04). No other lectin pathway protein levels or polymorphisms were associated with disease manifestations, low complement C3 and/or C4 levels, or inflammatory markers. CONCLUSIONS: This study does not support a relevant role for several lectin pathway complement proteins in the pathogenesis of SSc. Higher FCN-2 levels were however associated with Scl-70 autoantibody positivity, interstitial lung involvement, and digital vasculopathy. Elevated MBL levels were associated with renal crisis.